Development of an enhanced anti-pan-N-formylmethionine-specific antibody - Dasom Kim; Kyu-Sang Park; Cheol-Sang Hwang (BioTechniques, 2025)
Both bacterial and eukaryotic ribosomes can initiate protein synthesis with formylmethionine (fMet), but detecting fMet-bearing peptides and fMet-bearing proteins has been challenging due to the lack of effective anti-pan-fMet antibodies. Previously, we developed a polyclonal anti-fMet antibody using a fMet-Gly-Ser-Gly-Cys pentapeptide that detects those fMet-bearing peptides and fMet-bearing proteins regardless of their sequence context. In this study, we significantly improved the antibody’s specificity and affinity by using a mixture of fMet-Xaa-Cys tripeptides (Xaa, any of the 20 amino acids) as the immunogen. This newly optimized anti-fMet antibody is a powerful, cost-effective tool for detecting fMet-bearing proteins across species. Furthermore, this approach provides a foundation for developing anti-pan-specific antibodies targeting other N-terminal modifications through acylation, alkylation, oxidation, arginylation, etc.